Ethics for A-Level - Dimmock, Mark (Open Book Publishers, 2017)
"What does pleasure have to do with morality? What role, if any, should intuition have in the formation of moral theory? If something is â simulatedâ , can it be immoral? This accessible and wide-ranging textbook explores these questions and many more. Key ideas in the fields of normative ethics, metaethics and applied ethics are explained rigorously and systematically, with a vivid writing style that enlivens the topics with energy and wit. Individual theories are discussed in detail in the first part of the book, before these positions are applied to a wide range of contemporary situations including business ethics, sexual ethics, and the acceptability of eating animals. A wealth of real-life examples, set out with depth and care, illuminate the complexities of different ethical approaches while conveying their modern-day relevance. This concise and highly engaging resource is tailored to the Ethics components of AQA Philosophy and OCR Religious Studies, with a clear and practical layout that includes end-of-chapter summaries, key terms, and common mistakes to avoid. It should also be of practical use for those teaching Philosophy as part of the International Baccalaureate. Ethics for A-Level is of particular value to students and teachers, but Fisher and Dimmockâ s precise and scholarly approach will appeal to anyone seeking a rigorous and lively introduction to the challenging subject of ethics."